Analysis of the coherent and turbulent stresses of a numerically simulated rough wall pipe - Chan L.; MacDonald M.; Chung D.; Hutchins N.; Ooi A. (Institute of Physics Publishing, 2023)
Boundary layer flow; Boundary layers; Fluid mechanics; Quay walls; Reynolds number; Secondary flow; Wall flow; Boundary layer thickness; Dispersive components; Rough wall flows; Roughness elements; Topological features; Triple decomposition; Turbulent stress; Wall pipe; Atmospheric thermodynamics